"I Don't Like to Make a Big Thing out of It": A Qualitative Interview-Based Study Exploring Factors Affecting Whether Young People Tell or Do Not Tell Their Friends about Their IBD. (11th June 2020) - Carter, Bernie; Rouncefield-Swales, Alison; Bray, Lucy; Blake, Lucy; Allen, Stephen; Probert, Chris; Crook, Kay; Qualter, Pamela
Abstract : Inflammatory Bowel Disease (IBD) describes a group of conditions that includes Crohn's disease and ulcerative colitis. Unlike some chronic conditions, to a greater or lesser extent, IBD is hidden from or invisible to others which enables concealment of the condition, especially when stigma is associated with the condition. Concealment or nondisclosure allows a means of identity management. Disclosure of a chronic condition is not a single event, and it is dependent on many factors. There is little literature that specifically addresses stigma and/or disclosure in relation to children and young people with IBD. An in-depth qualitative study was undertaken, framed by Interpretive Description and using interviews, friendship maps, and photographs within a participatory framework. Public and patient involvement and engagement (PPIE) was undertaken throughout (inception to dissemination) the study. Young people aged 14-25 years with IBD who had participated in the survey phase of the larger study self-selected to participate in interviews that focused broadly on friendship and feelings of social connectedness. Data were analysed using an iterative, interpretive approach. Preliminary themes were developed and these were explored further, and then tentative theoretical connections about friendship were developed. One superordinate theme focused on disclosure. Thirty-one young people (16 males, 15 females, mean age 18.7 years; 24 Crohn's, 7 colitis) participated in the interviews (of these, five created friendship maps and six utilised photographs). Three discrete, but interlinked, themes were generated, revealing young people's experiences of disclosure: to tell or not to tell; controlling the flow: the who, when, what, and how of telling; and reactions and responses to telling: anticipated and actual. Decisions about telling friends about having IBD are challenging for many young people. Having control over disclosure is not always possible, and the potential consequences can feel risky. However, most young people had positive experiences of disclosure and gained support from friends and romantic partners. Most young people downplayed the seriousness of their IBD, revealing some facets of their condition, aiming to sustain their self-identity. Only one young person had been given professional support to disclose. Provision of support and opportunities to discuss whether, when, who, and how to tell friends and what the risks and benefits may be is something that could be woven into an ongoing and wider person-centred dialogue between young people and health professionals within routine clinic visits.